Identifikasi Kandungan Senyawa Aktif Antibakteri Ekstrak Etanol 70% Bunga Cengkeh (Syzigium Aromaticum) Dalam Menghambat Pertumbuhan Bakteri Cutibacterium Acnes - Ratu Restu Casayora; Hendra Tarigan Sibero; Hesti Yuningrum; Tri Umiana Soleha (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: Acne (acne vulgaris) is caused by infection with the Cutibacterium acnes bacteria which is often treated with synthetic antibiotics, but long-term use can cause resistance. Clove flowers (Syzygium aromaticum) are known to contain active compounds such as eugenol, flavonoids, tannins and alkaloids which have the potential to act as natural antibacterials. This study aims to identify the active compound content and test the antibacterial activity of clove flower extract against C. acnes. Method: Experimental research was conducted using the post-test only control group design method. The bacterium used was Cutibacterium acnes. Clove flower powder was extracted with 70% ethanol using the maceration method, then tested for antibacterial activity using the well method. There were four concentration treatments: 25%, 50%, 75%, and 100%, alongside a positive control (clindamycin) and a negative control (aquadest). Results: Clove flower extract contains alkaloids, flavonoids, tannins, phenols, saponins, terpenoids and steroids. The Kruskal-Wallis statistical test results showing a significant difference (p < 0.001). Discussion: The antibacterial effectiveness of clove flowers is caused by the synergistic activity of active compounds, especially eugenol and tannin, which work by damaging cell membranes, inhibiting metabolic enzymes, and causing leakage of bacterial cell contents. Conclusion: Clove flower extract (Syzygium aromaticum) has strong antibacterial activity against Cutibacterium acnes.